An effective performance of dynamic and ad-hoc on-demand routing protocols for mobile ad-hoc networks under NS environment. (4th April 2020) - Lanka, Surekha; Ikechukwu, Ilogu
Mobile ad hoc network (MANET) is a popular emerging wireless network and plays vital role to maintain the routing demands in wireless network. AODV and DYMO are on-demand routing protocols that was designed to meet various needs of MANET such as security, mobility, flexibility etc. IETF listed on-demand routing protocols in a varying speed of nodes, mobility, and performance metrics. In this paper, we discussed behaviour of the two main on-demand routing protocols in network simulation environment, while sending packets from source to destination under free space and two ray propagation models by varying packet rate. We analysed the performance metrics of MANET in the following heading; average jitter, average end-to-end delay, packet delivery ratio, and throughput are compared with percentage of nodes packet drops.